Working hours and mental health in Australia: evidence from an Australian population-based cohort, 2001–2012. Issue 8 (22nd June 2015) - Milner, Allison; Smith, Peter; LaMontagne, A D
Abstract : Objectives: This paper assesses the impact of working less than or more than standard full-time hours on mental health, as well as possible differences in this relationship by gender and skill level. Methods: The study design was a longitudinal cohort with 12 annual waves of data collection over the period 2001–2012, yielding a sample of 90 637 observations from 18 420 people. Fixed effects within-person regression was used to control for time invariant confounding. The Mental Component Summary of the Short Form 36 (SF-36) measure was used as the primary outcome measure. Working hours over the preceding year was measured in five categories with standard full-time hours (35–40 h/week) as the reference. Results: Results indicated that when respondents were working 49–59 h (−0.52, 95% CI −0.74 to −0.29, p<0.001) and 60 h or more (−0.47, 95% CI −0.77 to −0.16, p=0.003) they had worse mental health than when they were working 35–40 h/week (reference). The difference in mental health when working 49–59 h was greater for women than for men. There were greater declines in mental health in relation to longer working hours among persons in higher compared to lower occupational skill levels. Conclusions: Study results suggest the need for employers and governments to regulate working hours to reduce the burden of mental ill health in the working population.